Pengaruh Leverage, Likuiditas, Ukuran Perusahaan, dan Fixed Assets Intensity Terhadap Revaluasi Aset Tetap (Studi Empiris pada Perusahaan Aneka Industri yang Terdaftar di BEI Tahun 2014-2018) - Yulianti Nur Fauziah; Hadi Pramono (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2020)
This study aimed to examine the effect of leverage, liquidity, firm size, and fixed assets intensity on fixed assets revaluation. The sample in this study was a company manufacturing various industry sectors listed on the Indonesian Stock Exchange during 2014-2018 period. Methods of data collection using purposive sampling. The analytical method of research used logistic regression analysis method. These results indicate that the variable leverage has a negative effect on fixed assets revaluation and firm size positive effect on fixed assets revaluation. While fixed assets intensity and liquidity have not effect on fixed asset revaluation.